DUSMA KOTA BANJARMASIN SEBAGAI WAJAH PERUBAHAN SUKU DAYAK DUSUN DAN MAANYAN UNTUK MEMPERTAHANKAN EKSISTENSI DIRI DI KOTA BESAR - Keloso; Maria Apriana Angela; Lia Afriliani; Hendra Hendra (Jurnal Teologi Pambelum, 2022)
The primary focus of the research is to identify the elements of wedding’s customary law and the subjects of social-cultural considerations that are underlying DUSMA’s changes and adaptabilities. It was a basic to maintain the existence and identity, building and empowering the culture of DUSMA Banjarmasin. This research is a descriptive study with a qualitative approach. The data collection processes include library research, observation, and interviewing. The subjects of this research are members of DUSMA Banjarmasin and figures named Dayak Dusun and Maanyan who live in Banjarmasin. Information and informants selected by purposive sampling and snowball sampling. The findings present that DUSMA Banjarmasin is accommodating the inspirations of Dayak Dusun and Maanyan people in Banjarmasin. Moreover, DUSMA Banjarmasin preserved Maanyan’s culture and language. DUSMA is a community based on association. DUSMA represents the customary laws, especially the wedding law that involves the collective consciousness of the family institution. The members of DUSMA in Banjarmasin constantly experience the process of enculturation and cultural socialization from generation to generation. The acknowledgement of the existence of DUSMA Banjarmasin by the society, church, and government is an important basic to maintaining the existence and identity of DUSMA Banjarmasin until now. Through biblical approaches, DUSMA Banjarmasin is a faith seeking fellowship and brotherhood in the midst of the Dayak Dusun and Maanyan communities in Banjarmasin. Therefore, the spirit of mira pakat bulat atei (unit in mutual deliberations) will have been creating the atmosphere of fellowship-brotherhood in DUSMA for supporting, giving solutions, and working together in goodness one to another (Gen. 11:1–9; 1 Thess. 5:12–22).